The Effects of Self-Efficacy on Motivation of Reading English Academic Text - Fuad Hasyim (Universitas Ahmad Dahlan, 2018)
The motivation of reading the academic text, especially in the English language, has been a problem for students of higher education. Whereas, reading ability is one of the important factors of students’ successful learning. This research aims to analyze the role of student’s self-efficacy in the level of motivation to read the textbooks in the English Language. This research applied quantitative approach. The population of this research is the whole students majoring in Management, Faculty of Economics, Universitas Islam Indonesia, that take Basic Academic Reading course in the first semester. The research’s primary data was collected by closed questionnaire, and supported by structured interviews (by 90% response rate). Meanwhile, the sampling technique used is purposive random sampling, and data analysis method used is Pearson Product Moment’s correlative coefficient. The result of this research revealed that students’ Self-Efficacy (SE) has a significant positive influence on their Motivation in Interest Aspect (MI), Motivation in Dedication Aspect (MD), and Motivation in Self-confidence Aspect (MC).